CORRELATION OF SODIUM, POTASSIUM, AND CALCIUM SERUM LEVELS AND MOTOR FUNCTION OUTCOME WITH ISCHEMIC STROKE PATIENTS IN HAJI ADAM MALIK GENERAL HOSPITAL, MEDAN - Ranintha br Surbakti, Alfansuri Kadri & Irina Kemala Nasution (International Journal of Research Science and Management, 2020)
Background: Ischemic stroke is the second caused of death at the age of more than 60 years and is a major cause of disability in adults. Disability is caused by motor disorders, nearly 80% of ischemic stroke patients experience motor disturbances. Stroke patients are also often found electrolyte disturbances that affect the clinical outcome of ischemic stroke patients. Objective: To determine correlation of sodium, potassium, and calcium serum levels on admission with motor function outcome of ischemic stroke patients. Research Methods: This study was a cross-sectional study selected with consecutive sampling techniques, where patients diagnosed with ischemic stroke treated at Haji Adam Malik General Hospital Medan who met the exclusion and inclusion criteria were included in this study. The study began from March to June 2020. Results: This study was conducted on 33 samples consisting of 18 men and 15 women with an average age of 59.85 ± 10.91 years. There was no significant relationship between serum sodium levels at admission with MAS scores (p= 0.945) with very weak correlation strength (r= 0.013). There was no significant relationship between serum potassium levels at admission with MAS score (p= 0.225) and weak correlation strength (r= 0.217). There was a significant relationship between serum calcium levels at admission with MAS scores (p= 0.001) with moderate correlation strength (r= 0.536) Conclusion: There is no correlatiaon between serum sodium and potassium levels with motor function outcome.There is a correlatiaon between serum calcium levels and motor function outcome.